2002
DOI: 10.1121/1.1479148
|View full text |Cite
|
Sign up to set email alerts
|

Time reversed reverberation focusing in a waveguide

Abstract: Time reversal mirrors have been applied to focus energy at probe source locations and point scatterers in inhomogeneous media. In this paper, we investigate the application of a time reversal mirror to rough interface reverberation processing in a waveguide. The method is based on the decomposition of the time reversal operator which is computed from the transfer matrix measured on a source-receiver array [Prada et al., J. Acoust. Soc. Am. 99, 2067-2076 (1996)]. In a similar manner, reverberation data collecte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
22
0

Year Published

2003
2003
2016
2016

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 55 publications
(22 citation statements)
references
References 17 publications
0
22
0
Order By: Relevance
“…Studies on time-reversal in waveguides 10,11 suggested that when the dispersed waves resulting from a transducer being excited by a pulse are time-reversed and re-emitted, wave re-compression occurs at the source location, giving rise to a high amplitude pulse. However, the effect of dispersion on wave re-compression has not been addressed.…”
Section: Introductionmentioning
confidence: 99%
“…Studies on time-reversal in waveguides 10,11 suggested that when the dispersed waves resulting from a transducer being excited by a pulse are time-reversed and re-emitted, wave re-compression occurs at the source location, giving rise to a high amplitude pulse. However, the effect of dispersion on wave re-compression has not been addressed.…”
Section: Introductionmentioning
confidence: 99%
“…9,10 This decomposition is also a means to separate the echo of a target from ground reverberation 11 and it was used to achieve reverberation focusing and nulling. 12,13 Recent at sea experiments confirm the efficiency of the DORT method for detection and focusing in a shallow water environment. 14,15 However, the aforementioned studies only considered isotropic scatterers.…”
Section: Introductionmentioning
confidence: 86%
“…6 The reverberation then can be treated as a single ͑extended͒ source problem in array processing. This suggests that a single snapshot would permit obtaining an estimate of the transfer function vector when a͒ there is a strong reverberation return, i.e., the high reverberation-to-noise and/or reverberation-to-echo case.…”
Section: Reverberation Nulling: Descriptionmentioning
confidence: 99%
“…5 The other approach to enhance active target detection is reverberation nulling recognizing that focusing and nulling are complementary. Lingevitch et al 6 recently have shown in simulation that backscattering from the rough water-bottom interface can serve as a surrogate probe source in time reversal. The concept is based on the fact that a time-gated portion of reverberation provides an estimate of the transfer function vector between a TRM array and the range cell along the bottom.…”
Section: Introductionmentioning
confidence: 99%